Le fratture della paletta omerale nei bambini - Pavone, V.; Lucenti, L.; Farsetti, P. (Lo Scalpello - Journal, 2018)
DISTAL HUMERAL FRACTURES IN CHILDRENDistal humeral fractures are common injuries of the elbow in children. The diagnosis is based on clinical evidence andradiographic examination; other investigations are rarely necessary. Undisplaced fractures need a conservativetreatment, while surgical treatment is recommended in most severe cases. It is generally performed by closed or openreduction and internal fixation with K-wires. These types of fractures can lead to early and late complications thatneed to be recognised and treated as soon as possible to avoid disabling conditions.